Deconvolution Analysis of the Non-Ionic Iomeprol, Iobitridol and Iodixanol Contrast Media-Treated Human Whole Blood Thermograms: A Comparative Study - Elek Telek; Zoltán Ujfalusi; Miklós Nyitrai; Péter Bogner; András Lukács; Tímea Németh; Gabriella Hild; Gábor Hild (Diagnostics, 2023)
To study the effect of non-ionic contrast media on anticoagulated and non-anticoagulated human whole blood samples, calorimetric measurements were performed. The anticoagulated plasma showed the greatest fall in the total ΔH after Iodixanol treatment. The plasma-free erythrocytes revealed a pronounced shift in the Tmax and a decrease in the ΔH of hemoglobin and transferrin. The total ΔH of Iodixanol treatment showed the highest decline, while Iomeprol and Iobitridol had fewer adverse effects. Similarly, the non-anticoagulated samples revealed a decrease both in the Tmax and the ΔH of albumin and immunoglobulin-specific transitions. The total ΔH showed that Iodixanol had more influence on the serum. The serum-free erythrocyte samples resulted in a significant drop in the Tmax of erythrocyte and transferrin (~5–6 °C). The ΔH of deconvolved hemoglobin and transferrin decreased considerably; however, the ΔH of albumin increased. Surprisingly, compared to Iomeprol and Iobitridol treatments, the total ΔH of Iodixanol was less pronounced in the non-anticoagulated erythrocyte samples. In sum, each non-ionic contrast medium affected the thermal stability of anticoagulated and non-anticoagulated erythrocyte proteins. Interestingly, Iodixanol treatment caused more significant effects. These findings suggest that conformational changes in blood components can occur, which can potentially lead to the increased prevalence of cardiovascular dysfunctions and blood clotting.